1993
DOI: 10.1016/s0022-5347(17)36198-0
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective European Organization for Research and Treatment of Cancer Genitourinary Group Randomized Trial Comparing Transurethral Resection Followed by a Single Intravesical Instillation of Epirubicin or Water in Single Stage Ta, T1 Papillary Carcinoma of the Bladder

Abstract: A total of 431 eligible patients with solitary, primary or recurrent stages Ta and T1 transitional cell carcinoma of the bladder was included in a randomized multicenter trial to compare a single intravesical instillation of 80 mg. epirubicin with water given immediately after resection, with respect to the disease-free interval and recurrence rate. The interval to initial recurrence was significantly better in favor of the epirubicin group. After a mean followup of 2 years it became evident that the recurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
151
0
5

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(160 citation statements)
references
References 11 publications
4
151
0
5
Order By: Relevance
“…However, when these eff ects are transferred to an in-vivo model there are several issues: tumour cell compounds might not be safely accessible to osmotic damage, and osmotic eff ects on healthy bladder mucosa are unclear. In the EORTC randomised trial, 29 the eff ect of an early single instillation of epirubicin 80 mg in 50 mL saline versus 50 mL sterile water was assessed in 399 patients at low risk for recurrence. The interval to initial recurrence was signifi cantly in favour of the epirubicin group and the recurrence rate per year reduced by nearly 50% after a mean follow-up of 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, when these eff ects are transferred to an in-vivo model there are several issues: tumour cell compounds might not be safely accessible to osmotic damage, and osmotic eff ects on healthy bladder mucosa are unclear. In the EORTC randomised trial, 29 the eff ect of an early single instillation of epirubicin 80 mg in 50 mL saline versus 50 mL sterile water was assessed in 399 patients at low risk for recurrence. The interval to initial recurrence was signifi cantly in favour of the epirubicin group and the recurrence rate per year reduced by nearly 50% after a mean follow-up of 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…15 Oostelinck et al first demonstrated that a single instillation clearly prevented recurrence for patients with a single tumor. 6 Tolley et al stated that a single instillation can prevent recurrences of patients with either a single or multiple tumors. In this study, we demonstrated the prophylactic effect of THP for patients with a single superficial bladder carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, the immediate instillation of a chemotherapeutic agent after TUR-Bt has become an alternative option since Oostelinck et al and Tolley et al reported on its validity. 6,7 Developed in Japan, THP is a new anthracycline derivative. Be-cause THP is more rapidly absorbed into the tumor cells than doxorubicin resulting in higher intracellular concentrations, even a small dosage may exert greater prophylactic effect.…”
mentioning
confidence: 99%
“…There are controversial results from studies evaluating the adjuvant role of a single, postoperative intravesical instillation of chemotherapy regimens such as epirubicin, mitomycin C and gemcitabin within 24 hours after transurethral resection (Tolley et al, 1988;Oosterlinck et al, 1993;Hall, 1997;Brocks et al, 2005 of NMIBC recommend that all patients receive one immediate instillation of chemotherapy after TUR. In patients at low risk of recurrence and progression, no further treatment is recommended prior to a subsequent recurrence.…”
Section: Introductionmentioning
confidence: 99%